Making war on bodies militarisation, aesthetics and embodiment in international politics - Baker, Catherine (Advances in critical military studies, 2020)
This vibrant collection of essays reveals the intimate politics of how people with a wide range of relationships to war identify with, and against, the military and its gendered and racialised norms